Biosafety Profiling of “Makann”, a Bi-herbal Formulation in Histopatology of the Brain and Uterus - Itemire, Anne Oghenekevwe; Idu, MacDonald; Enitome, Bafor Evi; Eze, Gerald Ikechi; Gabriel, Benjamin Ogunma (Darul Yasin Al Sys, 2025)
The biosafety of Garcinia kola and Carica papaya aqueous root extract